1997
DOI: 10.1007/s11745-997-0036-x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of long‐chain n‐3 fatty acids in tissues and enhanced bone marrow cellularity with docosahexaenoic acid feeding in post‐weanling Fischer 344 rats

Abstract: We wanted to examine the effects of an oil rich in docosahexaenoic acid (DHA), without eicosapentaenoic acid, on the composition of membrane phospholipid in a variety of tissues. Our in vitro studies had previously shown that DHA could modify glucose and nucleoside transport in cells in culture and also increase selectivity of the nucleoside drug, arabinosylcytosine (araC) toward tumor cells. Here we wanted to examine what effect DHA supplementation would have in the whole animal in terms of the chemosensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 24 publications
7
47
1
Order By: Relevance
“…Diagram adapted from Poulsen and Kruger (2007) [152]. [12,13]. In line with this finding, the PUFA composition of cell membranes is dependent on the dietary intake to a great extent.…”
Section: Figuresupporting
confidence: 61%
See 2 more Smart Citations
“…Diagram adapted from Poulsen and Kruger (2007) [152]. [12,13]. In line with this finding, the PUFA composition of cell membranes is dependent on the dietary intake to a great extent.…”
Section: Figuresupporting
confidence: 61%
“…AA preserves MSC numbers through COX-2 mediated synthesis of PGE 2 by inhibiting apoptosis [70]. DHA and possibly also other n-3 LCPUFA-rich diets may elevate or preserve bone mass through increasing MSC numbers [13] and through enhanced expression of key transcription factors such as Cbfa1 and osterix [33,92] that enhance differentiation of pre-osteoblasts into mature osteoblasts. Expression of both Cbfa1 and osterix is enhanced by IGF-1, TGF-β1, BMP and moderate amounts of PGE 2 [92], all of which result from diets rich in n-3 LCPUFA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study [23], an increased production of PGE2 in tibia of chicks given a semipurified diet containing soya bean oil, high in w-6 fat was associated with a lower rate of bone formation compared with that of chicks fed a low dietary ratio of w-6/w-3 fatty acids. In a further study [24], rats fed with a lower dietary ratio of w-6/w-3 fat showed increased bone marrow cellularity and bone strength. These studies indicate that w-6/w-3 fatty acid ratio of diet appears to be important in bone metabolism, and may be responsible for fracture due to trivial trauma in our patients.…”
Section: Osteoporosis and Cardiovascular Diseasementioning
confidence: 83%
“…Further support for the role of polyunsaturated fatty acids in the pathogenesis of osteoporosis and hip fracture may be provided from the experimental studies [22][23][24][25]. In a experimental study [22], 15 rats were fed identical diets except that w-6/w-3 ratio differed.…”
Section: Osteoporosis and Cardiovascular Diseasementioning
confidence: 99%